Corporate Social Responsibility and Governance: The Role of Executive Compensation. Issue 2 (20th April 2020) - Cavaco, Sandra; Crifo, Patricia; Guidoux, Aymeric
Abstract : This article examines the relationship between corporate governance and corporate sustainability by focusing on an essential component of companies' governance structure: executive compensation programs. We propose an original empirical strategy based on a large set of the biggest capitalizations in Organization for Economic Cooperation and Development (OECD) countries over the period 2004–2018, with explicit measures of how companies integrate into executive managers' remuneration precise criteria of corporate social responsibility, an incentive scheme called corporate social responsibility (CSR) contracting. Our results show that proposing executive compensation programs including CSR criteria has a negative impact on financial performance, and a large positive impact on extra‐financial performance based on the following dimensions: relationship with customers and suppliers, and community involvement. Second, we explore the moderating role of the corporate governance model by distinguishing the impact between firms with a shareholder or stakeholder corporate governance model and reveal significant differences in the impact of CSR contracting. For firms with a stakeholder corporate governance model, CSR contracting is no longer associated with a fall of financial performance and has a large positive impact on human resources, environmental, and human rights performance. On the other hand, CSR contracting has a negative impact on financial performance but no impact on extra‐financial performance for firms with a shareholder corporate governance model.